Pengaruh Pengaruh Faktor Internal dan Eksternal Terhadap Return Saham Perusahaan Sektor Pertambangan yang Terdaftar di ISSI - Abdul Azid; Dadang Hermawan; Fifi Afiyanti Tripuspitorini; Radia Purbayati (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to examine the influence of the company's internal factors consisting of return on equity (ROE), Debt to Equiy Ratio (DER), and firm size (Firm Size) as well as external factors consisting of inflation, exchange rates, and Gross Domestic Product (GDP) on stock returns of mining sector companies listed on the Indonesian Sharia Stock Index (ISSI) for the 2016–2020 period. The data used is secondary data for the 2016-2020 period sourced from the Indonesia Stock Exchange (IDX), Bank Indonesia (BI), and the Central Statistics Agency (BPS). Samples were taken using a purpose sampling technique in order to obtain 13 companies that became the research sample. The data analysis technique used is multiple linear regression analysis using Eviews 12. The results show that simultaneously ROE, DER, firm size, inflation, exchange rate, and GDP have an effect on stock returns. while partially ROE, DER, firm size and exchange rate have no effect on stock returns. Inflation and GDP have a negative and significant effect on stock returns.